Cyberporn and censorship: constitutional barriers to preventing access to internet pornography by minors. - Simon, Glenn E. (Journal of Criminal Law & Criminology)
Part of a special section on the Supreme Court is presented. In Reno v. ACLU, the Court found two provisions of the Communications Decency Act of 1996 to be unconstitutional due to their vagueness and the chilling effect their application would have on Internet communications. It is argued that any future attempt to regulate sexually explicit Internet transmissions must be drafted with adequate specificity in order to eliminate ambiguity as to the scope of its enforcement. The government's contention that this regulation is justified as an exercise of its zoning power is rejected.